Correlating tooth anatomy with the age and sex of human filipino skulls and cadavers - Matute, Bernard; Murjani, Bhabita (Adviser).
Forensic dentistry is a branch of dentistry that is not given much attention to in the country. So much information from this branch of dentistry can be used in identifying deceased victims of disasters and crimes. In many situations, the age and sex of a Filipino individual cannot be determined because the body is mangled beyond recognition. The aim of this study was to correlate tooth anatomy with the age and sex of human Filipino skulls and cadavers. The research was performed on skulls and cadavers, mainly from the department of Anatomy in the University of the Philippines Manila, and the department of Anthropology in the University of the Philippines Diliman. The chi-square test was done to see if sex and shape of crown are dependent on one another. A regression equation was formulated to determine if there is a correlation between the cervico-occlusal height of tooth number 16 and age. Various other statistical tests were done to determine if there is a correlation between different measurements of tooth number 11 and tooth number 16 and age. After all the different tests were done, it was found that there is a correlation between the age and sex of human Filipino skulls and tooth anatomy. Regarding age, as the cervico-occlusal height of tooth number 16 decreases, age increases. Given the cervico-occlusal measurement of tooth number 16, the age of the sample may be estimated using the formula AGE = 138.395 - 13.243 (CQ16), where CQ16 is the cervico-occlusal height of tooth number 16. Regarding sex, it was found that the shape of tooth number 11 and sex are dependent on each other.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Tooth -- Anatomy and histology